2019
DOI: 10.18502/kls.v4i11.3854
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chicken Bone Powder Supplementation during Pregnancy and Lactation on the Calcium Level of Rat Pups’ Teeth

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In that study, chicken BEP suspension was given to pregnant Sprague Dawley rats from the first day of pregnancy to the second week of parturition. The calcium level of rat pups' teeth in the chicken BEP supplementation group was significantly higher than the control (Atmokotomo et al 2019). The higher calcium bioavailability of chicken BEP, when compared with the same calcium content in traditional calcium-rich diet sources and some forms of commercial calcium salts was explained by the fact that chicken BEP does not contain substances such as fiber, phytate, and oxalate which can bind to calcium becoming insoluble complexing agents and consequently can interfere with the absorption of calcium in the gut (Whisner et al 2014).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In that study, chicken BEP suspension was given to pregnant Sprague Dawley rats from the first day of pregnancy to the second week of parturition. The calcium level of rat pups' teeth in the chicken BEP supplementation group was significantly higher than the control (Atmokotomo et al 2019). The higher calcium bioavailability of chicken BEP, when compared with the same calcium content in traditional calcium-rich diet sources and some forms of commercial calcium salts was explained by the fact that chicken BEP does not contain substances such as fiber, phytate, and oxalate which can bind to calcium becoming insoluble complexing agents and consequently can interfere with the absorption of calcium in the gut (Whisner et al 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Calcium-rich diet sources that are well-known and commonly consumed include dairy products (such as milk, yogurt, and cheese), grains, and green leafy vegetables. However, the only problem with these calcium sources is that these foods contain some substances, for example, fiber, phytic acid, and oxalic acid that have a strong binding affinity to calcium, inhibiting its absorption (Atmokotomo et al 2019). Chicken bone, a by-product from the poultry industry, contains high calcium but does not contain substances that inhibit calcium absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Atmokotomo et al, 2019, did an intervention on rat's pups and observed the effect of blood calcium levels on the tooth development and found a marked difference in their teeth morphology. Those who had optimum calcium levels also had wellmineralized teeth, amount of calcium in their teeth was also higher as compare to those whose calcium levels were reduced (19) .…”
Section: Discussionmentioning
confidence: 92%